Szkolne przygotowanie uczniów staropolskich kolegiów jezuickich do służby politycznej - Nowicki, Michał (Biuletyn Historii Wychowania, 2024)
The primary purpose of this article is to show the opportunities offered by old-Polish Jesuit education in preparing young people for political service, from the historical and pedagogical perspective. Due to the scarcity of fundamental studies on everyday school practice in Jesuit colleges of the First Polish Republic, the text will analyze selected source texts, possibly from various periods and school centers. Of course, the framework of the article does not allow for thorough comparative studies on such an extensive issue that deserves a monographic study. To avoid generalities, the paper will focus on showing specific content standards in the Jesuits school circle. The source material on everyday school life in the old-Polish period is abundant and still unsatisfactorily used, to mention school notebooks and lecture scripts, school panegyric literature, and programs of theater plays (these enjoy the greatest interest).